Muay Thai exercises improve quality of life, love of life and self-control - Sahin, Oktay; Yilmaz, Coskun; Sezer, Sureyya Yonca; Sahin, Fatma Nese; Ceylan, Levent; Celikel, Baha Engin; Kirikoglu, Nagihan (Frontiers Media Sa, 2025)
Background The existing research on Muay Thai sports has focused predominantly on the physiological effects of training, with limited attention devoted to the study of quality of life, love of life and self-control. The present study examined the effects of Muay Thai exercises on quality of life, love of life and self-control scores in healthy male subjects. Methods The present study comprised 50 healthy sedentary male subjects. The subjects were randomly divided into two groups: one group engaged in Muay Thai training (MTT), while the other group served as a control group (CON). The sample sizes for the MTT and CON groups were both 25. The MTT group participated in basic Muay Thai training, while the CON group continued their normal life regime. The SF-12 quality of life scale, love of life scale and multidimensional self-control scale were administered before and after the six-week training period. Results The study concluded that the six-week Muay Thai training program had a significant effect on quality of life levels, with 13.23% (p = 0.003) and 21.93% (p < 0.001) of participants demonstrating improvements in physical and mental scores, respectively. In terms of self-control levels, the program was found to have a significant effect on initiation and inhibition scores, with increases of 23.78% (p = 0.001) and 24.69% (p < 0.001), respectively. It was concluded that had a significant effect on the sub-dimensions of the Love of Life scale with increases of Positive Attitude Toward Life (PAWL) 18.63% (p < 0.001), Happy Results of the Love of Life (HRLL) 20.11% (p < 0.001) and Meaningfulness of Life (ML) 15.62% (p < 0.001), respectively. However, no significant differences were detected in any of the scales within the control group. Conclusion Muay Thai exercises had a positive effect on quality of life, love of life and self-control levels in healthy male subjects. By providing valuable insights into how Muay Thai exercise affects quality of life, love of life, and self-control, this research can guide future intervention and program design in the context of sport psychology.
Keywords: combat sports; mental health; Muay Thai; love of life; self-control; quality of life; sport psychology